Classification and usage of medical protective face mask during the COVID-19 epidemic (新型冠状病毒肺炎疫情防控期间防护医用口罩分类与使用对策) - CHEN Ya (陈亚); WANG Yuena (王岳娜); XU Yuanle (许远乐) (中西医结合护理)
Medical protective face mask is an essential protective material for infection control and prevention and ensuring public health during the COVID-19 epidemic. Based on the analysis of technical specification and related interpretation on medical protective mask at home and aboard , this paper summarized the classification and usage of medical protective mask, and provide references for establishment of standardized process for using medical protective mask. (新型冠状病毒肺炎疫情防控期间, 医用防护口罩是防止病毒感染、保护人群健康安全必不可缺的防护物资。本文根据国内外防护口罩技术规范及解读, 对防护口罩的分类和使用方法进行了初步的总结, 以期为进一步规范防护口罩使用方法提供参考。)